2022
DOI: 10.3390/nu14235054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Different Dietary Weight Loss Strategies on Risk Factors for Urinary Stone Formation and Cardiometabolic Risk Profile in Overweight Women

Abstract: Overweight has been suggested to increase the risk of kidney stone formation. Although weight reduction might affect risk factors for urolithiasis, findings on the impact of different dietary weight loss strategies are limited. This randomized, controlled study evaluated the effect of a conventional energy-restricted modified diet with (MR group) or without meal replacement (C group) on risk factors for stone formation in overweight women without a history of urolithiasis. Of 105 participants, 78 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Among the five components of MetS, elevated waist circumference, low HDL-C, and elevated blood glucose were independent influencing factors of kidney stones, and their OR values were 1.205 (95% CI: 1.085–1.337), 1.222 (95% CI: 1.105–1.351) and 1.335 (95% CI: 1.202–1.482), respectively. Similar to this study, several studies found an association between MetS and kidney stones ( 34 , 35 ) and confirmed that each of the five components of MetS increased the risk of kidney stones individually ( 13 , 14 , 36 - 38 ). For example, similar findings were obtained in a cross-sectional analysis in South Korea, where kidney stones were diagnosed by ultrasound or CT.…”
Section: Discussionsupporting
confidence: 90%
“…Among the five components of MetS, elevated waist circumference, low HDL-C, and elevated blood glucose were independent influencing factors of kidney stones, and their OR values were 1.205 (95% CI: 1.085–1.337), 1.222 (95% CI: 1.105–1.351) and 1.335 (95% CI: 1.202–1.482), respectively. Similar to this study, several studies found an association between MetS and kidney stones ( 34 , 35 ) and confirmed that each of the five components of MetS increased the risk of kidney stones individually ( 13 , 14 , 36 - 38 ). For example, similar findings were obtained in a cross-sectional analysis in South Korea, where kidney stones were diagnosed by ultrasound or CT.…”
Section: Discussionsupporting
confidence: 90%
“…Individually tailored approaches to weight reduction could reduce the risk of UA stone formation in patients with overweight and other components of the metabolic syndrome [ 43 ]. A randomized, controlled study on the impact of a conventional energy-restricted, lacto-vegetarian-oriented mixed diet with or without meal replacement on urinary risk factors for kidney stone formation and cardiometabolic risk profile in non-stone forming overweight women observed a higher relative weight loss, a higher rate of responders, and a significant decrease in serum UA concentration and the relative supersaturation of UA in the meal replacement group [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having an elevated Body Mass Index (BMI) is the most commonly used way to gauge if one is at risk of forming kidney stones ( 7 , 8 ), which can be caused by being overweight. However, BMI is not without its drawbacks ( 9 ).…”
Section: Introductionmentioning
confidence: 99%